Jesus and the angels: A comparative reading of Hebrews 1:1–4 in light of Ewe angelology - Sakitey, Daniel; Van Eck, Ernest (Hervormde teologiese studies, 2024)
This article examines the phrase, tosoutō kreittōn genomenos tōn angelōn (Heb 1:4a) (having become as much superior to the angels) in the exordium of the epistle to the Hebrews in the light of Ewe angelology. The article employs both comparative and mother tongue hermeneutical approaches as its methodologies. An exegetical analysis of the cosmic superiority of Christ over angels in Hebrews 1:4a was carried out to situate the text in its historical and literary contexts. This was followed by an excursus on angels to explore the angelic world of the text, and a comparative discussion with angelology motif in Ewe cosmology. Finally, the article assesses the cosmic supremacy of Christ over the angelic world of the Ewe against the backdrop of the continuous quest for spiritual protection in Ewe-Ghanaian spirituality today. The quest for spiritual protection in popular Ewe-Ghanaian Christianity today stems from the perception that Christ’s cosmic superiority over the cosmos he created and owns including angelic beings alone is not enough and that one would need to resort to other mediums to enhance access to God for quicker solutions to one’s predicaments. This has resulted in the introduction of syncretic elements in spirituality. To cure the syncretic elements in Ewe Christian spirituality, this article makes the following proposals: Firstly, the preaching (kerygma) and teaching (didache) of the gospel message must be given priority in the pulpit. Secondly, Christian educators must constantly emphasise Christ’s superiority and his exclusive mediatory function over Ewe cosmic beings to ensure that old and new converts to Christianity view him alone as sufficient for their spiritual development.Contribution: The article contributes to the academic knowledge of the priestly Christology in Hebrews situating it within the context of mother tongue biblical hermeneutics.